The SIforAGE project: social innovation for active and healthy ageing - Marques, S. (2015)
This article describes the SIforAGE Project – an innovative approach to an aged Europe. The SIforAGE consortium is integrated by a wide range of stakeholders working together in order to promote an active and healthy ageing. ISCTE-IUL is one of the partners involved in this project and has been developing an important role in different work packages: (i ) Technology Experience cafés aiming to involve older people in the development of technological devices addressed to them (which had a general positive impact regarding the attitudes and intentions of older participants to use technologies); (ii ) conceptualization and development of an intervention program (imAGES) to fight ageism among children (the pilot program developed in Lisbon revealed the efficacy of this program); (iii ) analysis of the anti-age discrimination laws (AADL’s) in five European countries (these laws are present in the European countries analyzed but it was identified a gap between legislation and its compliance); (iv) organization of a call for prize on social innovation research on the ageing field (which was widely disseminated across several European countries). Through these several activities, the SIforAGE project constitutes a step forward towards the development of a more inclusive society, a society for all «ages».